Amnion Membrane Transplantation: A Therapy for Persistent Epithelial Defect as A Result of Neurotrophic Keratitis: Poster Presentation - Case Report - Resident - Nathasya Maharani Susilo; Patriotika Muslima; Elfa Ali Idrus; Arief Akhdestira Mustaram; Angga Fajriansyah (Majalah Oftalmologi Indonesia, 2023)
Introduction : A persistent epithelial defect (PED) is a failure of re-epithelialization and complete healing of the cornea. The primary goal of PED treatment is to create a favorable environment for corneal wound healing. Amniotic membrane transplants (AMT) become one of the refractory cases treated for PED. This study aims to report AMT as therapy for a PED. Case Illustration : A fifty-six-year-old male presents with a chief complaint of redness and pain in the left eye in the last2 weeks. The patient complained of blurred vision, tearing, and foreign body sensations. An ophthalmology examination of the left eye revealed that it was close to face finger counting in visual acuity and had a persistent epithelial defect, corneal edema, descemet fold, and a decrease in corneal sensation. The patient was diagnosed with PED and received autologous serum eye drops, levofloxacin eye drops, vitamin A palmitate eye gel, and acyclovir 400mg twice a day, but did not respond adequately. AMT was planned for the patient. The patient's pain level improved one week after surgery. Discussion : The most common symptom of PED is pain. There are various etiological factors for PED. Neurotropic keratitis has emerged as one of the causes of PED. Management for PED is carried out sequentially according to the protocol. Conclusion : Amniotic membrane transplantation has become an alternative therapy for PED. The amniotic membrane provides re-epithelialization of the cornea and anti-inflammatory properties. The prognosis for AMT as a therapy for PED is quite good.